2023
DOI: 10.7759/cureus.34533
|View full text |Cite
|
Sign up to set email alerts
|

Do Platelet-Rich Plasma Injections for Knee Osteoarthritis Work?

Abstract: Background: Recent evidence suggests a benefit in platelet-rich plasma injections (PRP) for the knee in the management of mild to moderate osteoarthritis (OA). There is a reported reduction in pain, stiffness, and improved function. However, there is very little level-one literature available that supports this practice and conclusively proves a benefit gained throughout the course. Three main randomized control trials (RCTs) conducted in North America are often referenced and cited to prove their efficacy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Bansal et al found that a concentration of 10 billion platelet was necessary for any chondroprotective effects to be visible at the 1-year mark [12]. Research has shown that PRP trials are prone to the placebo effect as mild OA cases tend to see significant improvement in pain scores that are not as evident in moderate-to-severe cases of OA [36]. On the other hand, this may simply suggest that PRP therapy is more effective at earlier stages of OA and that any regenerative abilities decrease with disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Bansal et al found that a concentration of 10 billion platelet was necessary for any chondroprotective effects to be visible at the 1-year mark [12]. Research has shown that PRP trials are prone to the placebo effect as mild OA cases tend to see significant improvement in pain scores that are not as evident in moderate-to-severe cases of OA [36]. On the other hand, this may simply suggest that PRP therapy is more effective at earlier stages of OA and that any regenerative abilities decrease with disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 13 (56%) responses given by ChatGPT version 4 provided resources available for patient review, with some sources cited in multiple responses. Of the resources cited, 7 (53%) were direct links to PubMed ® indexed studies, comprising of one randomized control trial (RCT), one retrospective study, three literature reviews, and two meta-analyses [23][24][25][26][27][28][29]. The remaining sources cited by ChatGPT consisted of a link to patient education material generated by the American Academy of Orthopaedic Surgeons (AAOS), one private website dedicated to patient education with physician-written, peer-reviewed articles, as well as four websites by privately run US-based orthopedic practices [30][31][32][33][34][35].…”
Section: Discern Scorementioning
confidence: 99%
“…Scientific studies have shown that PRP's application can lead to improvements in cartilage repair and pain reduction. While its efficacy can vary based on factors such as the severity of the cartilage damage and the patient's overall health, PRP offers a minimally invasive approach to stimulate the body's natural healing mechanisms and support the restoration of cartilage tissue [74][75][76].…”
Section: Growth Factor and Cytokine Therapymentioning
confidence: 99%